Quantification of ammonia oxidation rates and the distribution of ammonia-oxidizing Archaea and Bacteria in marine sediment depth profiles from Catalina Island, California - Beman, J. Michael; Bertics, Victoria J.; Braunschweiler, Thomas; Wilson, Jesse (Frontiers in Microbiology, 2012)
Microbial communities present in marine sediments play a central role in nitrogen biogeochemistry at local to global scales. Along the oxidation-reduction gradients present in sediment profiles, multiple nitrogen cycling processes (such as nitrification, denitrification, nitrogen fixation, and anaerobic ammonium oxidation) are active and actively coupled to one another—yet the microbial communities responsible for these transformations and the rates at which they occur are still poorly understood. We report pore water geochemical (O2, NH4+, NO3-) profiles, quantitative profiles of archaeal and bacterial amoA genes, and ammonia oxidation rate measurements, from bioturbated marine sediments of Catalina Island, California. Across triplicate sediment cores collected offshore at Bird Rock and within Catalina Harbor, oxygen penetration (0.24-0.5 cm depth) and the abundance of amoA genes (up to 9.30 x 107 genes g-1) varied with depth and between cores. Bacterial amoA genes were consistently present at depths of up to 10 cm, and archaeal amoA was readily detected in Bird Rock cores, and Catalina Harbor cores from 2008, but not 2007. Although detection of DNA is not necessarily indicative of active growth and metabolism, ammonia oxidation rate measurements made in 2008 (using isotope tracer) demonstrated the production of oxidized nitrogen at depths where amoA was present. Rates varied with depth and between cores, but indicate that active ammonia oxidation occurs at up to 10 cm depth in bioturbated Catalina Harbor sediments, where it may be carried out by either or both ammonia-oxidizing Archaea and Bacteria.